The Resting Potential and K+ Currents in Primary Human Articular Chondrocytes - Maleckar, Mary M.; Clark, Robert B.; Votta, Bartholomew; Giles, Wayne R. (Frontiers in Physiology, 2018)
Human transplant programs provide significant opportunities for detailed in vitro assessments of physiological properties of selected tissues and cell types. We present a semi-quantitative study of the fundamental electrophysiological/biophysical characteristics of human chondrocytes, focuses on K+ transport mechanisms, and their ability to regulate to the resting membrane potential, Em. Patch clamp studies on these enzymatically isolated human chondrocytes reveal a consistent expression of at least three functionally distinct K+ currents, as well as transient receptor potential (TRP) currents. The small size of these cells and their exceptionally low current densities present significant technical challenges for electrophysiological recordings. These limitations have been addressed by parallel development of a mathematical model of these K+ and TRP channel ion transfer mechanisms that can reveal their contributions to Em. In combination these experimental results and simulations yield new insights into: (i) the ionic basis for Em and its expected range of values; (ii) modulation of Em by the unique articular joint extracellular milieu; (iii) some aspects of TRP channel mediated depolarization-secretion coupling. (iv) some of the essential biophysical principles that regulate K+ channel function in the ‘chondrons’. The chondron denotes the chondrocyte and its immediate extracellular compartment. The presence of discrete localized surface changes or zeta potentials at the chondrocyte surface that is regulated by the cell metabolism and modulates interactions of chondrocytes with the extracellular matrix. Semi-quantitative analysis of these factors in chondrocyte/chondron function may yield insights into progressive osteoarthritis.